Review of recent radon research in Ireland, OPTI-SDS project and its impact on the National Radon Control Strategy. (September 2020) - Fuente, Marta; Long, Stephanie; Fenton, David; Hung, Le Chi; Goggins, Jamie; Foley, Mark
Abstract: Radon is a radioactive gas originating from uranium, present in all rocks and soils in the Earth's Crust; emanating from the ground, radon can be released into the atmosphere. It is the greatest source of natural radioactivity exposure for the population and, as declared by the World Health Organization (WHO), the leading cause of lung cancer only after smoking. Although radon is a natural gas, its accumulation provoking elevated indoor radon levels is a result from building practices and thus, not natural. In Ireland, exposure to radon is estimated to be responsible for approximately 14% of all lung cancers, which is equivalent to around 300 lung cancers annually. In 2011, an interagency group was established in Ireland to develop a strategy to address indoor radon exposure, considered a significant public health concern. In 2014 a National Radon Control Strategy (NRCS) for Ireland was first published, giving a list of recommendations to be accomplished in a 4-year period Phase 1. A series of research actions to achieve the effective implementation of the strategy were conducted, including the development of a research project (OPTI-SDS) on the optimum specifications for radon mitigation by soil depressurisation systems. An overview of Phase 1 of the NRCS is presented, including outcomes from the research work carried out. Highlights: BSS Directive 2013/59/EURATOM requires national action plans to address radon risks. Radon is the greatest source of natural radioactivity exposure for the population. Indoor radon exposure is the leading cause of lung cancer after smoking. A National Radon Control Strategy (NRCS) for Ireland was developed in 2014. Research to support the effective implementation of the NRCS was conducted.